MAGNETOBIOSTRATIGRAPHY OF THE STURA DI LANZO FOSSIL FOREST SUCCESSION (PIEDMONT, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Along the Stura di Lanzo River, 20 km north of Turin (Italy), several large mummified stumps in growth position crop out, thus providing a well-preserved example of fossil forest. This is formed by conifers which bear the Glyptostrobus europaeus type of cone and foliage as well as the Glyptostroboxylon rudolphii wood-type. Stratigraphic and plant taphonomic analyses of the outcropping succession clearly indicate that the palaeoenvironment was a densely-vegetated swamp, laying nearby one or more active fluvial/deltaic channels, in which coarse cross-bedded sands were deposited. The fossils are embedded in fine-grained continental sediments referred to the «Villafranchiano» unit, a term used in the Piedmont region (north-western Italy) to designate coastal to continental deposits which conformably overlay Pliocene marine successions. In this paper we present new data which better characterize the chronostratigraphy of the Stura di Lanzo Fossil Forest (FF) succession and similar deposits studied at the Front Canavese (FR) site, 10 km to the NE. The integrated magnetobiostratigraphic approach, applied to both outcropping sections and subsurface deposits, permits to attribute the FF to the subchron Kaena. On the basis of these new magnetobiostratigraphic data, a strongly supported correlation between the FF and the Villafranchian "type-section" of Villafranca d'Asti is proposed. Furthermore, the well-constrained FF chronostratigraphy adds new data to the Middle Pliocene vegetation history, since an adequate palaeofloral documentation for the time interval corresponding to subchron Kaena was still lacking in Italy.
Keywords: Fossil forest; Pliocene; Plant assemblage; Magnetostratigraphy; Italy